Fatigue Life Analysis of FSO Anchor Chain with Corrosion Effect - Dewinta Putri Cahyaningtyas; Nur Syahroni; Rudi Walujo Prastianto; Eko Budi Djatmiko; Murdjito Djatmiko; Hafizh Muhammad Naufal Shidqi (International Journal of Marine Engineering Innovation and Research, 2023)
In this study, the authors analyze the fatigue life of the anchor chain used to secure the Gamkonora FSO to the seabed. The objective is to determine the operational lifespan of the anchor chain by considering its fatigue life. The research begins with an analysis of the movement of the Gamkonora FSO under environmental loads in both free-floating and moored conditions to determine the tension in each anchor chain. Next, the anchor chain tension is calculated for various corrosion levels, namely 0%, 5%, 10% and 15%. Subsequently, the tension range and damage ratio values are determined using the T-N curve method based on Palmgren Miner’s failure law, with failure estimation carried out using the rainflow counting method. The numerical modeling results reveal that the largest translational motion behavior of the FSO occurs during heave motion, reaching 1.409 m/m, while the largest rotational motion is observed during roll motion, with a value of 3.463 deg/m when the FSO is fully loaded. The maximum tension recorded in the anchor chain is 1,695.14 kN at heading 90° under 0% corrosion conditions, with a safety factor of 4.53. Furthermore, the cumulative damage value from the T-N curve is obtained, with the largest value recorded as 0.0702. Based on the cumulative damage, the fatigue life of the anchor chain is estimated to be 14.25 years during its operational lifespan.